Quantitative analysis of the pigment composition of macrophage aggregates in the spleen of chub (Squalius cephalus L., 1758) from the river Crn Drim. Influence of sex and season - Pavloski, Stefan; Ivanova, Lozenka; Jordanova, Maja; Dinevska-Ќovkarovska, Suzana; Rebok, Katerina (Macedonian Journal of Ecology and Environment, 2020)
The research examined the quantity of total macrophage aggregates, as well as the quantity of macrophage aggregates with different pigment composition, in the spleen of chub from the river Crn Drim. In total, 156 fish were collected for qualitative and quantitative assay. In addition to the relative and total volume, and the number of macrophage aggregates per unit area, the fish were measured for body weight and total length, condition factor, spleen weight and spleensomatic index. All examined parameters were interpreted in relation to season and sex. In males collected in the spring-summer season, general relative and total volume increase, as well as the relative volume of macrophage aggregates that contained lipofuscin/ceroid and the combination of lipofuscin/ceroid and melanin was noted, compared to values measured for males collected in the autumn-winter. In relation to sex, values measured for males were also higher when compared to values measured for females, although insignificantly. Since the fish were collected from relatively unpolluted sites, the results from this research can be used as reference point for the use of macrophage aggregates in the studies for biomonitoring of the aquatic ecosystems.